162k views
5 votes
Simplifying Expressions

3. Which of the following expressions is the simplified form of the expression below?
(x^3+2x^2+5) - (8x^2 - 4x + 6)
A. 10x -11
B. 9x^3-- 2x^2 +11
C. 7x^2 - 2x^2 -1
D. x^3-6x^2+ 4x - 1

User Rangana
by
5.5k points

1 Answer

2 votes

Answer:

As


\left(x^3+2x^2+5\right)-\left(8x^2-4x+6\right)=x^3-6x^2+4x-1

Therefore, option D is the correct answer is.

Explanation:

Given the expression


\left(x^3+2x^2+5\right)\:-\:\left(8x^2\:-\:4x\:+\:6\right)

solving to simplify the expression


\left(x^3+2x^2+5\right)\:-\:\left(8x^2\:-\:4x\:+\:6\right)


=x^3+2x^2+5-\left(8x^2-4x+6\right)
\mathrm{Remove\:parentheses}:\quad \left(a\right)=a


=x^3+2x^2+5-\left(8x^2-4x+6\right)


=x^3+2x^2+5-8x^2+4x-6

Group like terms


=x^3+2x^2-8x^2+4x+5-6


\mathrm{Add\:similar\:elements:}\:2x^2-8x^2=-6x^2


=x^3-6x^2+4x+5-6


\mathrm{Add/Subtract\:the\:numbers:}\:5-6=-1


=x^3-6x^2+4x-1

Therefore, the simplified form of the expression is


\left(x^3+2x^2+5\right)-\left(8x^2-4x+6\right)=x^3-6x^2+4x-1

Therefore, option D is the correct answer is.

User Sachleen
by
5.4k points